Herring oil rich in long-chain monounsaturated fatty acid (C22: 1n-11) lowers plasma lipids and modulates fatty acid composition, oxidation, and inflammation in rats - Nundal, Camilla H.; Tungland, Siri Lunde; Bakke, Hege G.; Bohov, Pavol; Aloysius, Thomas A.; Rustan, Arild C.; Bjørndal, Bodil; Brønstad, Aurora; Øyen, Jannike; Brandt, Suzanne; Sydnes, Magne O.; Nygård, Ottar; et al. (Frontiers in Nutrition, 2025)
IntroductionMarine oils and fatty fish rich in long-chain n-3 polyunsaturated fatty acids (PUFAs), such as eicosapentaenoic acid (C20:5n-3, EPA) and docosahexaenoic acid (C22:6n-3, DHA), have been reported to enhance fatty acid (FA) oxidation and reduce plasma triacylglycerol and cholesterol levels. In addition to n-3 PUFAs, herring oil contains long-chain monounsaturated fatty acids (MUFAs), including cetoleic acid (C22:1n-11). This study aimed to investigate the effect of consuming CETO3® oil—derived from herring and naturally rich in n-3 PUFAs and cetoleic acid—on plasma lipid levels, FA composition, mitochondrial oxidation, and inflammation in rats.MethodsRats were fed low-fat diets supplemented with 5% CETO3® oil (experimental) or soy oil (control) for 10 weeks. Plasma lipid profile (triglycerides (TG), total cholesterol, low-density lipoprotein (LDL) and high-density lipoprotein (HDL)) and FA composition in both liver and plasma were analyzed. In vitro substrate oxidation was assessed using ¹⁴CO₂-trapping in human liver and human myotubes. Safety parameters, including blood hematology, glucose tolerance, and organ weights, were also measured.ResultsCETO3® supplementation decreased plasma levels of total fat (−58%), TG (−55%), total cholesterol (−41%), and LDL cholesterol (−45%), while increasing the ratio of HDL to LDL cholesterol (46%). Supplementation also increased hepatic and plasma levels of long-chain n-3, n-9, and n-11 MUFAs, including C22:1n-11, and decreased n-6 FA accumulation. The reduction in saturated long-chain FAs in both the liver and plasma indicated increased hepatic peroxisomal and mitochondrial activity. Furthermore, increased oleic acid oxidation was observed in human myotubes in the presence of C20:1n-11 and C20:1n-9.DiscussionThese findings suggest that intake of CETO3® oil lowers plasma lipids, potentially through enhanced peroxisomal and mitochondrial FA oxidation. The shift in FA composition, with reduced n-6 FAs and increased n-3 and n-11 MUFAs, indicates an anti-inflammatory effect. CETO3® oil also appears safe, as hematological parameters, glucose tolerance, and organ weights remained unaffected.